Confronting a post-pandemic new-normal—threats and opportunities to trust-based relationships in natural resource science and management. (15th March 2023) - Muir, A.M.; Bernhardt, J.R.; Boucher, N.W.; Cvitanovic, C.; Dettmers, J.M.; Gaden, M.; Hinderer, J.L.M.; Locke, B.; Robinson, K.F.; Siefkes, M.J.; Young, N.; Cooke, S.J.
Abstract: Natural resource governance is inherently complex owing to the socio-ecological systems in which it is embedded. Working arrangements have been fundamentally transformed throughout the COVID-19 pandemic with potential negative impacts on trust-based social networks foundational to resource management and transboundary governance. To inform development of a post-pandemic new-normal in resource management, we examined trust relationships using the Laurentian Great Lakes of North America as a case study. 82.9% ( n  = 97/117) of Great Lakes fishery managers and scientists surveyed indicated that virtual engagement was effective for maintaining well-established relationships during the pandemic; however, 76.7% ( n  = 89/116) of respondents indicated in-person engagement to be more effective than virtual engagement for building and maintaining trust. Despite some shortcomings, virtual or remote engagement presents opportunities, such as: (1) care and nurturing of well-established long-term relationships; (2) short-term (1–3 years) trust maintenance; (3) peer-peer or mentor-mentee coordination; (4) supplemental communications; (5) producer-push knowledge dissemination; and, if done thoughtfully, (6) enhancing diversity, equity, and inclusion. Without change, pre-pandemic trust-based relationships foundational to cooperative, multinational, resource management are under threat. Highlights: A post-pandemic new-normal is emerging in natural resource fields. Only 26% of fishery professionals established trust-relationships during the pandemic. 76% of survey respondents said in-person was more effective than virtual engagement. Trust relationships key to multinational resource management are under threat. Governments should prioritize trust-relationships in a post-pandemic new-normal.